Intuitive Choices Lead to Intensified Positive Emotions: An Overlooked Reason for “Intuition Bias”? - Kirkebøen, Geir; Nordbye, Gro H. H. (Frontiers in Psychology, 2017)
People have, for many well-documented reasons, a tendency to overemphasize their intuitions and to follow them, even when they should not. This “intuition bias” leads to several kinds of specific intuitive biases in judgments and decision making. Previous studies have shown that characteristics of the decision process have a tendency to “leak” into the experience of the choice outcome. We explore whether intuitive choices influence the experience of the choice outcomes differently from “nonintuitive,” analytic choices. Since intuition is feeling based, we examine in particular if intuitive choices have stronger affective consequences than nonintuitive ones. Participants in two scenario studies (N = 90; N = 126) rated the feelings of decision makers who experienced a conflict between two options, one intuitively appealing and another that appeared preferable on analytic grounds. Choosing the intuitive alternative was anticipated to lead to somewhat more regret after negative outcomes and, in particular, much more satisfaction with positive outcomes. In two autobiographical studies, one with psychology students (N = 88) and the other with experienced engineers (N = 99), participants were asked to provide examples of choice conflicts between an intuitive and a nonintuitive option from their own private or professional lives. Both groups showed a tendency to report stronger emotions, in particular positive, after intuitive choices. One well-established explanation for intuition bias focuses on the nature of people’s anticipated negative counterfactual thoughts if their decisions were to turn out badly. The present data indicate that intuitive choices intensify positive emotions, anticipated and real, after successful outcomes much more than negative emotions after failures. Positive outcomes are also more commonly expected than negative ones, when we make choices. We argue that markedly amplified emotions, mediated by stronger personal involvement, in the positive outcomes of intuitive versus nonintuitive choices, is an overlooked reason for intuition bias.